Turkish Islam-Nationalism Under AKP: A New Model for the Muslim World? - Tobing, Fredy B. L.; Nurwijoyo, Agung (Global: Jurnal Politik Internasional, 2020)
The Justice and Development Party’s (Adalet ve Kalkınma Partisi/AKP) activities in bridging Islam and nationalism marks a historic milestone in Turkey’s democracy. Throughout its two decades-long leadership, AKP, under Recep Tayyip Erdoğan’s leadership, demonstrated that nationalism and Islam do not clash with Turkey’s stance on secularism. Such understanding provides AKP with a strategic leverage, both at the domestic and international level, especially within the Muslim world. Reflecting upon Rustow’s democratic transition model and Ibn Khaldun’s classic conceptualisation on ashabiyyah, this article attempts to comprehend how Turkish nationalism is formulated within its relations with Islam as AKP’s political roots. Aside from consolidating its political power at the domestic level, this article suggests that the Islam and democracy synthesis provides an opportunity for Turkey to strengthen its political image and position in the region. In a much broader context, this article attempts to contribute to academic discussions on the relationship between religion and states which undergo the process of democratisation.